Somatoform disorder as a predictor of interstitial cystitis/bladder pain syndrome: Evidence from a nested case-control study and a retrospective cohort study. Issue 18 (May 2017) - Chen, I-Chun; Lee, Ming-Huei; Lin, Hsuan-Hung; Wu, Shang-Liang; Chang, Kun-Min; Lin, Hsiu-Ying
Abstract : Abstract: Interstitial cystitis/bladder pain syndrome (IC/BPS) has several well-known comorbid psychiatric manifestations, including insomnia, anxiety, and depression. We hypothesized that somatoform disorder, which is a psychosomatic disease, can be used as a sensitive psychiatric phenotype of IC/BPS. We investigated whether somatoform disorder increases the risk of IC/BPS. A nested case-control study and a retrospective cohort study were followed up over a 12-year period (2002–2013) in the Taiwan Health Insurance Reimbursement Database. In the nested case-control study, 1612 patients with IC/BPS were matched in a 1:2 ratio to 3224 controls based on propensity scores. The odds ratio for somatoform disorder was calculated using conditional logistic regression analysis. In the retrospective cohort study, 1436 patients with somatoform disorder were matched in a 1:2 ratio to 2872 patients with nonsomatoform disorder based on propensity scores. Cox regression analysis was used to estimate the hazard ratio associated with the development of IC/BPS in patients with somatoform disorder, and the cumulative survival probability was tested using the Kaplan–Meier analysis. We found that the odds ratio for somatoform disorder was 2.46 (95% confidence interval [CI], 1.05–5.76). Although the average time until IC/BPS development in the control subjects was 11.5 ± 1.3 years, this interval was shorter in patients with somatoform disorder (6.3 ± 3.6 years). The hazard ratio for developing IC/BPS was 2.50 (95% CI 1.23–5.58); the adjusted hazard ratio was 2.26 (95% CI 1.002–5.007). The patients and controls also differed significantly in their cumulative survival probability for IC/BPS (log rank P < .05). Evidence from the nested case-control study and retrospective cohort study consistently indicated that somatoform disorder increases the risk for IC/BPS. Our study suggests that somatoform disorder can be used as a sensitive psychiatric phenotype to predict IC/BPS. Any past history of somatoform disorder should be documented while examining patients with IC/BPS.